KAMUS LENGKAP KOSAKATA INDONESIA BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract- Android is an operating system that is open source which provides the freedom for developers to develop an application. With the advantages of the android operating system, will help a lot of Android-based smartphone users to enjoy a variety of applications, one such application is complete dictionary vocabulary Indonesia. The main purpose of the application of the full dictionary Indonesian vocabulary is to assist them in finding a translation of vocabulary to artikata Indonesian, English, synonyms and antonyms. The type of data used are secondary data where the data obtained from reference books and literature related to this thesis. There are several stages in the making of this application, the analysis, design, workmanship and evaluation of program models that have been produced. Lengap dictionary application android-based vocabulary of Indonesia, can be used on Android-based smartphones with minimal version 2.2. In testing these applications can run smoothly. Keywords: Android, dictionary, synonyms, antonyms